2005
DOI: 10.1093/toxsci/kfi192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organochlorine Insecticides on MAP Kinase Pathways in Human HaCaT Keratinocytes: Key Role of Reactive Oxygen Species

Abstract: Organochlorine pesticides (OCs) are reported as potential carcinogens in humans. The aim of this study was to investigate the effects of four OCs (dieldrin, endosulfan, heptachlor, and lindane) on mitogen-activated protein kinase (MAPK) cascades and more specifically to identify the mechanism underlying OC-induced ERK1/2 activation. Organochlorine pesticides increased phosphorylated Raf, MEK1/2, ERK1/2, and c-Jun in human HaCaT cells, but they had no effect on p38 MAPK activation. Moreover, blockade of Raf, ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 37 publications
9
33
0
1
Order By: Relevance
“…The complexities of the physiological roles of MAPK may be due partially to the duration of MAPK activities differentially regulating genes in various cell types. Activation of ERK1/2 by organochlorine pesticides has been reported in human keratinocytes (Ledirac et al, 2005). It has been suggested that in situations where ERK1/2 induces cell death, the activation tends to be sustained (Wang et al, 2000), which is the case under our experimental conditions.…”
Section: )supporting
confidence: 62%
See 1 more Smart Citation
“…The complexities of the physiological roles of MAPK may be due partially to the duration of MAPK activities differentially regulating genes in various cell types. Activation of ERK1/2 by organochlorine pesticides has been reported in human keratinocytes (Ledirac et al, 2005). It has been suggested that in situations where ERK1/2 induces cell death, the activation tends to be sustained (Wang et al, 2000), which is the case under our experimental conditions.…”
Section: )supporting
confidence: 62%
“…A critical role of ROS in organochlorine pesticidesinduced ERK1/2 activation, probably by stabilizing its phosphorylation, has been reported (Ledirac et al, 2005). It has been proposed that transient activation of ROS inactivates MAPK regulatory phosphatases, contributing to their activation, (Lee and Esselman, 2002).…”
Section: Page 22 Of 44 Toxicological Sciencesmentioning
confidence: 99%
“…PKC-mediated internalization also appears to reduce recycling of DAT pools and increase degradation via the lysosomal pathway (Daniels & Amara, 1999;Loder & Melikian, 2003), thereby decreasing the total DAT levels in the cell. Interestingly, dieldrin exposure in cells can lead to the activation of a specific PKC isoform Ledirac et al, 2005) which could explain the decreased DAT expression seen in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…The carcinogenic potential of pyrethroids was also reported on the murine model (9). A few recent studies revealed that besides blocking neurotransmission, both pyrethroids and organophosphate pesticides can cause immunosuppression and deregulation of many signalling molecules (10)(11)(12)(13)(14)(15). Organophosphates (derivatives of phosphonic acid) and systemic azole fungicides have profound cytotoxic activities, too (16,17).…”
mentioning
confidence: 99%